(untitled) (Tempo e Argumento, 2026)
This article submits the trajectory of the Tupinambá de Olivença Indigenous Territory to a hermeneutic-critical reading that bridges History and Law. Drawing on administrative, ethnographic and journalistic sources, we examine how narratives of dispossession—from the 1559 colonial massacre to contemporary land reclamations—produce legal meanings that alternately deny or reaffirm Tupinambá ancestry. The analysis foregrounds three convergent axes: land violence as a technology of silencing; agro-real-estate expansion as a reorganization of sovereignties over the Atlantic Forest; and a symbolic dispute that seeks to desubstantiate indigenous identity in order to legitimize the “time-mark” thesis. We show that the reclamations function simultaneously as cosmological gesture, subsistence practice and performative hermeneutic of article 231 of the Brazilian Constitution. Technical Note 01/2025-MPF, by recognizing the declaratory character of original rights, shifts the conflict from the factual to the normative plane, revealing the role of legal interpretation in the (de)construction of colonial violence. We conclude that Tupinambá resistance—anchored in collective memory and self-demarcation—rewrites the grammar of territory in contemporary Brazil and offers an analytical key for understanding Amerindian insurgencies that demand historical and environmental justice across Latin America. Keywords: Tupinambá de Olivença Indigenous Territory; indigenous demarcation; land reclamations; collective memory; Amerindian resistance. Versión en español Entre la tierra y la ley: Reclamaciones territoriales e insurgencia amerindia en la demarcación de la Tierra Indígena Tupinambá de Olivença ResumenEl artículo somete la trayectoria de la Tierra Indígena Tupinambá de Olivença a una lectura hermenéutico-crítica que articula Historia y Derecho. A partir de fuentes administrativas, etnográficas y periodísticas, examinamos cómo las narrativas de despojo—desde la masacre colonial de 1559 hasta las reclamaciones territoriales contemporáneas—producen sentidos jurídicos que ora niegan ora reafirman la ancestralidad tupinambá. El análisis destaca tres ejes convergentes: la violencia fundiaria como tecnología de silenciamiento; la expansión agro-inmobiliaria como reorganización de soberanías sobre la Mata Atlántica; y la disputa simbólica que intenta desustancializar la identidad indígena para legitimar la tesis del “marco temporal”. Demostramos que las reclamaciones operan simultáneamente como gesto cosmológico, práctica de subsistencia y hermenéutica performativa del art. 231 de la Constitución brasileña. La Nota Técnica 01/2025-MPF, al reconocer el carácter declarativo del derecho originario, desplaza el conflicto del plano fáctico al normativo, revelando el papel de la interpretación jurídica en la (de)construcción de violencias coloniales. Concluimos que la resistencia tupinambá, anclada en la memoria colectiva y la autodemarcación, reescribe la gramática del territorio en el Brasil contemporáneo y ofrece una clave analítica para comprender las insurgencias amerindias que exigen justicia histórica y ambiental en América Latina.